2001
DOI: 10.1097/00042192-200107000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of isoflavones extracted from red clover (Rimostil) on lipid and bone metabolism

Abstract: These results show that the administration of an isoflavone combination extracted from red clover was associated with a significant increase in high-density lipoprotein cholesterol, a significant fall in apolipoprotein B, and a significant increase in the predominantly cortical bone of the proximal radius and ulna after 6 months of treatment. Interpretation of the results is undertaken cautiously because of the absence of a simultaneously studied control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(85 citation statements)
references
References 22 publications
1
81
1
2
Order By: Relevance
“…Our literature search identified 31 RCTs. Twenty-two studies were excluded because of lack of indices of interest (Agnusdei et al, 1997a, b;Gambacciani et al, 1997a, b;Potter et al, 1998;Alekel et al, 2000;Wangen et al, 2000;Clifton-Bligh et al, 2001;Katase et al, 2001;Anderson et al, 2002;Chiechi et al, 2002;Lucas et al, 2002;Chen et al, 2003Chen et al, , 2004Jones et al, 2003;Schult et al, 2003;Atkinson et al, 2004;Harkness et al, 2004;Olsen et al, 2004;Mori et al, 2004a, b), non-randomization (Dalais et al, 1998), lack of a control group (Agnusdei et al, 1997a, b), insufficient original data or baseline values (Gambacciani et al, 1997a, b;Khalil et al, 2002). Thus, nine studies with a total of 432 subjects were included in this meta-analysis, in which five studies had quality score of five; three studies had quality score of four and one study had quality score of three (Morabito et al, 2002;Uesugi et al, 2002;Yamori et al, 2002;Arjmandi et al, 2003Arjmandi et al, , 2005Dalais et al, 2003;Brooks et al, 2004;Mori et al, 2004a, b;Nikander et al, 2004) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Our literature search identified 31 RCTs. Twenty-two studies were excluded because of lack of indices of interest (Agnusdei et al, 1997a, b;Gambacciani et al, 1997a, b;Potter et al, 1998;Alekel et al, 2000;Wangen et al, 2000;Clifton-Bligh et al, 2001;Katase et al, 2001;Anderson et al, 2002;Chiechi et al, 2002;Lucas et al, 2002;Chen et al, 2003Chen et al, , 2004Jones et al, 2003;Schult et al, 2003;Atkinson et al, 2004;Harkness et al, 2004;Olsen et al, 2004;Mori et al, 2004a, b), non-randomization (Dalais et al, 1998), lack of a control group (Agnusdei et al, 1997a, b), insufficient original data or baseline values (Gambacciani et al, 1997a, b;Khalil et al, 2002). Thus, nine studies with a total of 432 subjects were included in this meta-analysis, in which five studies had quality score of five; three studies had quality score of four and one study had quality score of three (Morabito et al, 2002;Uesugi et al, 2002;Yamori et al, 2002;Arjmandi et al, 2003Arjmandi et al, , 2005Dalais et al, 2003;Brooks et al, 2004;Mori et al, 2004a, b;Nikander et al, 2004) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Our postmenopausal subjects had normal lipid levels, but displayed an increase in HDL-cholesterol during the isoflavone supplementation phase. This may be pertinent in light of the fact that, although one recent short-term study using the same purified red clover isoflavone pills found no effect on plasma lipid and lipoprotein concentrations (Nestel et al, 1999), other longer term studies using this supplement have demonstrated an effect of isoflavones on HDL 3 (Samman et al, 1999) in premenopausal women and total HDL (Knight et al, 1999;Clifton-Bligh et al, 2001) in menopausal and postmenopausal women. The apparent difference in these findings compared to those obtained with soy-derived isoflavones could be accounted for by the high levels of biochanin and formononetin in red clover isoflavone extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Atkinson and coworkers 41 found no significant difference in mammographic breast density after 12 months' administration of Promensil (43.5 mg/day isoflavones) compared with placebo in a study in 177 women (aged 49 to 65 years) with increased breast density, nor was there any statistically significant effect on estradiol, follicle-stimulating hormone (FSH), or luteinizing hormone levels. Clifton-Bligh and colleagues 42 found that Rimostil dosages up to 85.5 mg/day taken for 6 months did not increase endometrial thickness. Baber and coworkers 40 found no significant differences in serum estradiol, FSH, sex hormone-binding globulin, vaginal cytology, or endometrial thickness after 3 months' administration of Promensil 40 mg/day.…”
Section: Safetymentioning
confidence: 95%